Pengaruh Infrastruktur dan Kepadatan Penduduk Terhadap Penanaman Modal Asing Di Provinsi Jawa Tengah - Baihakil Aziz (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
Investment is an investment activity by an individual to companies that aim to get the maximum possible return for the investor. In this study, the researchers attempted to describe and estimate the effect of policy uncertainty, infrastructure, and population density on foreign investment in Central Java province. In this study using quantitative methods, the data used used multiple linear regression models using the ECM (Error Correctiom model) approach assisted by the E-views application obtained from the official website of the Central Java Statistics Agency. Then, the data is processed by testing the partial T, Multiple Determination Coefficients, and Simultaneous Tests in the short and long term. The results of the data management explain that 0.0182 where <0.05, so that it accepts H2 and in X2 it is 0.8320 > 0.05, so it rejects H3 which means that in the long term infrastructure and population density do not significantly affect investment foreigners in the province of Central Java. However, in the long term, infrastructure has a significant effect on foreign investment in Central Java province, while population density has no significant effect on foreign investment in Central Java province.